Դրվագներ ուրարտա–մուծածիրյան հարաբերությունների պատմությունից - Գրեկյան, Երվանդ («Զանգակ - 97»)
In the scientific lileralure it was long since discussed the significant role of the land/holy city of Musasir/Ardini in the formation of the Urartian State. The offered paper is the first part of the author's supervisions on the matter - the political relations of these slate formations during the whole length of the history. Especially, Ihe author focuses on the well-documented evenls - the military confrontation between the Urarlian Empire and the land of Musasir.
Keywords: Հայոց պատմություն